Muscle volume vs. anatomical cross-sectional area: Different muscle assessment does not affect the muscle size-strength relationship - Lanza, M. B.; Martins-Costa, H. C.; De Souza, C. C.; Lima, F. V.; Diniz, R. C.R.; Chagas, M. H. (Journal of Biomechanics, 2022)
Muscle volume (MV) and anatomical cross-sectional area (CSA) are used as measures of muscle-size, but determining these from magnetic resonance imaging (MRI) is a very time-consuming process. Additionally, it is unclear if the use of different muscle size assessments (all vs. reduced number of slices images) would impact the muscle size-strength relationship. Thus, this study aimed to investigate if muscle size calculation by using a reduced or all slices images from pectoralis major (PM) would maintain a similar muscle size-strength relationship with bilateral maximal dynamic and isometric contractions on a bench press exercise. Twenty-four healthy males underwent an MRI examination to measure PM muscle size, and maximal isometric and dynamic contractions (by one repetition maximum, 1RM) were performed. Correlations between maximal isometric voluntary force (MVF) and dynamic strength (1RM) with muscle size variables [three images from the largest part of PM (CSA3MAX), three images accounting for the shape -first image, middle image, final image- of the PM (CSA3), and MV] were performed. The correlation between 1RM with MV, CSA3, and CSA3MAX were 0.84, 0.832, and 0.727 (p < 0.001), respectively. The correlation between MVF with MV, CSA3, and CSA3MAX were 0.738, 0.733, and 0.604 (p < 0.001), respectively. Overall, PM MV and CSA3 exhibit a stronger and similar muscle size-strength relationship during maximal dynamic and isometric tests than CSA3MAX. Therefore, a reduced number of slices (CSA3) could be used as an alternative to considerably reduce the time of analysis without compromise muscle size-strength relationship.